Formation of aerobic granular sludge during the treatment of petrochemical wastewater. (August 2017) - Caluwé, Michel; Dobbeleers, Thomas; D'aes, Jolien; Miele, Solange; Akkermans, Veerle; Daens, Dominique; Geuens, Luc; Kiekens, Filip; Blust, Ronny; Dries, Jan
Highlights: Aerobic granulation was successfully obtained with petrochemical wastewater. Full granulation was achieved in 30 days with both strategies. Anaerobic feeding stimulated slow growing organisms. Aerobic granulation was obtained with O2 concentrations between 1 and 4 mg O2 .L −1 . Abstract: In this study, petrochemical wastewater from the port of Antwerp was used for the development of aerobic granular sludge. Two different reactor setups were used, (1) a completely aerated sequencing batch reactor (SBRae ) with a feast/famine regime and (2) a sequencing batch reactor operated with an anaerobic feast/aerobic famine strategy (SBRan ). The seed sludge showed poor settling characteristics with a sludge volume index (SVI) of 285 mL.g MLSS −1 and a median particle size by volume of 86.0 µm ± 1.9 µm. In both reactors, granulation was reached after 30 days with a SVI of 71 mL.g MLSS −1 and median granule size of 264.7 µm in SBRan and a SVI of 56 mL.g MLSS −1 and median granule size of 307.4 µm in SBRae . The chemical oxygen demand (COD) and dissolved organic carbon (DOC) removal was similar in both reactors and above 95%. The anaerobic DOC uptake increased from 0.13% to 43.2% in 60 days in SBRan .